POLA KEPEKAAN ANTIBIOTIK ISOLAT BAKTERI ENTEROBACTERIACEAE KONTAMINAN PADA SIKAT GIGI - Titi Lasmini; Trisna Anisha (Cross-border, 2020)
A toothbrush is a dental instrument used to maintain oral hygiene by removing bacteria on the surface of the teeth. Toothbrushes can be contaminated by Enterobacteriaceae from the bathroom environment and cause reinfection in the oral cavity. The purpose of this study was to determine the antibiotic susceptibility pattern of Enterobacteriaceae isolated from toothbrushes after 5 weeks of use. Bacteria were isolated on MacConkey agar and identified based on biochemical reaction tests. The antibiotic susceptibility test (Chloramphenicol, Gentamicin, Streptomycin, Ofloxacin, and Tetracycline) of the bacterial isolates was carried out by Kirby-Bauer disk diffusion method. Isolation of bacteria from toothbrushes on MC medium obtained Klebsiella sp, Escherichia coli, Serratia marcescens, and Enterobacter sp. The results of the antibiotic sensitivity test showed that Enterobacter sp. were sensitive to all of the antibiotics tested, while the other isolates had variations in the susceptibility pattern to the various antibiotics. Ofloxacin was the only tested antibiotic that can inhibit all bacterial isolates.